Characterization of palm oil clinker powder for utilization in cement-based applications. (15th March 2017) - Karim, Mohammad Razaul; Hashim, Huzaifa; Abdul Razak, Hashim; Yusoff, Sumiani
Highlights: POCP consist of inorganic oxides with small fraction of organic carbon. Microstructure analysis confirms that the particle of POCP is irregular in shape and porous in nature. Amorphisity hump occurs at the angular 2θ range of 10°–35° in XRD pattern. The crystallinity index of quartz in POCP is 0.97 which means that the quartz is partially disordered. Abstract: Palm oil clinker (POC) is a waste material produced as result of using palm oil shell and mesocarp fibers as fuel to run stream turbines in palm oil mills. The current practice is to dump this waste in open land or landfill sites, which leads to environmental problems. The characterization of such waste to identify its suitability as a cement replacement materials, can ultimately lead to lower carbon footprint concrete. This paper presents the results of a study on the physical properties (particle size, specific surface, specific gravity, loss of ignition, morphology), chemical composition, organic carbon, thermal stability and mineralogical composition of palm oil clinker powder (POCP). The characterization was carried out using particle size analyzer, scanning electron microcopy (SEM), X-ray fluorescence (XRF), field emission scanning electron microcopy and energy-dispersive X-ray analysis (FESEM-EDX), thermogravimetric analysis (TGA), total organic carbon (TOC) analysis, X-ray diffraction (XRD) and Fourier transform infrared spectroscopy (FTIR) techniques. From the laboratory works conducted results are defined and compared to existing literatures in tabulated form. The results of this extensive study on POCP characterization will provide guidance on future research work on utilization of POCP as a supplementary cementitious material in concrete.